Clinical practice guidelines: Loss of clinical freedom or a coming of age?. Issue 4 (1st July 2002) - Kitchener, H. C.
Abstract : When a woman presents to us with gynecological cancer our duty is to offer the most effective means of treatment; that which maximizes the potential for cure at the same maintaining or improving quality of life. For the majority of our patients we are able to contemplate cure but for many, particularly those with advanced ovarian cancer, this will not be possible although we can provide the prospect of several years of survival. In an international context our ability to provide optimal care depends largely on the healthcare resources which are affordable, and although in many parts of the world these are very limited, the same principles apply. This series of articles will put the spotlight on effective care in gynaecological oncology following an evidence based theme. The articles will be informative, punchy and provocative. The first of these contributions looks at clinical guidelines: what are they for, how do we produce them and is there any evidence that they do any good?